Achieving Health Equity by Addressing Legacies of Racial Violence in Public Health Practice. (March 2021) - Hudson, Darrell
Health equity means that everyone, regardless of their abilities, economic status, or race/ethnicity, has the opportunity to reach their optimal level of health. However, the inequitable distribution of resources, power, and privilege in the United States means that historically marginalized communities bear a disproportionate burden of poor health and disease. The COVID-19 pandemic has compounded the problem for Black Americans: already bearing an unequal burden of social, economic, and health inequities and experiencing systemic racism in various sectors of American life, Black Americans have been at even greater risk of COVID-19 transmission and severity of the disease. I use critical race theory (CRT) to show how key social and historical factors fuel racial health inequities. Further, I use key tenets of CRT to argue that redressing historical legacies of racism cannot be done without using a critical, race conscious lens and lifting up the voices of Black people.